Peta Kemampuan Keuangan Daerah - Hasan, Wahyudin; Jumiyanti, Kalzum R. (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
Regional autonomy makes the region be able to manage its region potential so that it will improve the aid of the community, facilitate public services, and regions given the opportunity to be able to compete to develop regions by legislation. However, the authority of regional autonomy does not necessarily make the area live independently in managing regional finance. This is the phenomenon of still high participation rates or the role of the central government in helping the regional government their managing regional finance activities through transfer funds. Therefore, this research was conduct to analyze regional financial capabilities for each region in the Province of Gorontalo considered this area has the potential of abundant natural resource wealth and has the opportunity to improve regional financial management. The analytical method are used Share and Growth analysis tools. The results showed that regional financial capabilities for each region in Gorontalo Province with a general quadrant method still in relatively evenly distributed portions. Quadrant 1 with the condition of the ideal area, which means this area is categorized by independent and potential regions, there are Gorontalo City, Gorontalo Regency, Boalemo Regency, and Bone Bolango Regency. Furthermore, there are two regions Pohuwato Regency and North Gorontalo Regency entering the quadrant 2 zone which means that the conditions are not ideal. But it needs to be underlined by this area to have the ability to develop its local potential so that the regional revenue has the opportunity to take a big role in financing total expenditure.